2021
DOI: 10.1111/hiv.13202
|View full text |Cite
|
Sign up to set email alerts
|

Humoral immune response following prime and boost BNT162b2 vaccination in people living with HIV on antiretroviral therapy

Abstract: Objectives People living with HIV (PLWH) with low CD4 T‐cell counts may be at a higher risk for severe coronavirus disease 2019 (COVID‐19) outcomes and in need of efficient vaccination. The World Health Organization (WHO) now recommends prioritizing PLHIV for COVID‐19 vaccination. Data on immune responses after messenger RNA (mRNA) vaccination in PLHIV in relation to CD4 counts are scarce. We aimed at assessing the humoral immune response in PLHIV after mRNA vaccination against COVID‐19. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
63
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(74 citation statements)
references
References 19 publications
8
63
3
Order By: Relevance
“…All the medians’ CD4 count was≥ 200 cells/µl (Supplementary material: Table 1). Sixteen studies reported the HIV viral load, among them, six studies included PLWH with viral load < 50 copies/ml [16, 45, 49, 51, 53, 54] and nine other studies included PLWH with viral load 58.1 to 95% suppressed [44, 46, 52, 55, 56, 58, 60, 61, 63, 65] ( Supplementary material: Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…All the medians’ CD4 count was≥ 200 cells/µl (Supplementary material: Table 1). Sixteen studies reported the HIV viral load, among them, six studies included PLWH with viral load < 50 copies/ml [16, 45, 49, 51, 53, 54] and nine other studies included PLWH with viral load 58.1 to 95% suppressed [44, 46, 52, 55, 56, 58, 60, 61, 63, 65] ( Supplementary material: Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The selected articles reported data from United States of America (n = 4) [48–50, 55], China (n=5) [52, 54, 59, 61, 64], South Africa (n = 3) [45, 46, 57], United Kingdom (n = 2) [16, 53], Canada (n=2) [ 47, 51], Italia (n=1) [58], Brazil (n =1) [56], Germany (n =1) [60], Israel (n = 1) [44], Sweden (n=1) [64], Taiwan (n=1) [65] and Russia (n = 1) [62] ( Figure 2 ). Ten studies used randomized control designs [16, 45, 46, 49, 50, 53, 54, 64, 64, 65], eight studies used prospective cohort designs [44, 47, 48, 51, 52, 56–58], two retrospective cohort studies [62, 63], two cross sectional studies [59, 61] and one case control study [55] ( Supplementary material: Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations